Stilasi Tanaman Carica Sebagai Sumber Ide Motif Batik - Jhundy, Brilliant Angellia; Wahyuningsih, Urip (Universitas Negeri Surabaya, 2023)
Stylization is a process of changing shape by looking at objects from various directions with stylization so as to create new motifs that are more varied and innovative without losing the characteristics of the source of the idea itself. Carica plants have contrasting colors between the leaves, fruit and stems. The large, shiny green leaves contrast with the bright yellow or orange fruit, making the carica plant look attractive and alluring to those who see it. This study aims to determine 1) the process of creating batik motifs using stylization techniques, 2) the results of stylized motifs applied to batik cloth. The method used is the Double Diamond Model which consists of 4 stages, namely: discover (find the uniqueness of the carica plant and the characteristics of the carica batik motif), define (summarize the findings in the form of a moodboard as the basis for making designs), develop (realize ideas by making stylized and batik designs by using the source of the idea of the carica plant), and deliver (production of carica motif batik cloth). This research resulted in 10 designs of carica batik motifs, and of the 10 designs, 1 design was selected which was embodied in the form of carica batik cloth.